151 - INFLUENCE OF THE SEMI-FINAL STAGE ON MOOD IN FEMALE HANDBALL ATHLETES AT UNISINOS CHAMPIONSHIP 2008 (Fiep Bulletin - online, 2011)
The research was conducted at the 21st edition of the Unisinos Championship, an event that occurred between 15 and 19 October 2008. Each year the University of Vale do Rio dos Sinos hosts sports teams from several institutions of higher education in Mercosul to play university games. Athletics, basketball games, soccer, futsal, handball, tennis, volleyball, beach volleyball, judo competitions, street skating, table tennis, chess and rustic matches were played in men and women categories, bringing together approximately 1200 students, coaches and leaders.The objective of this research was to determine which teams in the female handball category had more positive adjectives regarding the players' state of mind before the semifinals and to observe its influence on the outcome. Fifty-one women were evaluated in the adult category. A list of states of minds reduced and illustrated (LEA-RI) developed by Volp (2000) was used. The LEA-RI contains 14 adjectives and each of them is represented by a drawing of a face with its corresponding expression. According to Volp (2000) the LEA-RI was developed so that different populations (from children to elderly, literate or not) could answer it. Data collection was performed through an individual form, 40 minutes before each of the two semi-final games. For a descriptive statistical analysis of data, the absolute values of the mean were used. The results have shown that women handball players with high level of mood in the semi-final stage, reached the final stage.
Keywords: states of mind; semi-final; handball